ANALISIS KESALAHAN BAHASA BIDANG EJAAN DAN SINTAKSIS PADA KARANGAN NARASI BAHASA INDONESIA SISWA KELAS 5 MADRASAH IBTIDAIYAH - Wewen Andrianto; Devi Radnasari; Aninditya Sri Nugraheni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to describe syntactic errors in the areas of phrases, clauses, and sentences. Describe the factors that cause spelling and syntax errors in narrative essays of grade V students of MI Al Huda Karangnongko. This study uses a qualitative method. Data collection methods are carried out by interview, observation, and documentation. Data validity uses triangulation and source techniques. Data analysis uses the Miles and Huberman interactive model. The results of the study based on indicators in the phrase field there are errors, namely the use of regional languages, inappropriate prepositions, wrong word choices, excessive elements, excessive superlative influence, and the use of personal pronouns. Errors in clauses include the addition of prepositions between verbs and objects. Sentence errors include sentences without subjects, illogical sentences, ambiguous sentences, omission of conjunctions, and the use of foreign terms. Internal and external causes include a lack of understanding of the correct sentence structure, low reading interest, and the use of language in the surrounding environment. The implication of this study is that teachers must improve strategies to overcome syntactic errors by explaining the correct and proper writing procedures according to syntax.